Numerical methods for fractional order singular partial differential equations with variable coefficients - Elbeleze, Asma Ali; Kilicman, Adem; M. Taib, Bachok (Hindawi Publishing Corporation, 2014)
We implement relatively analytical methods, the homotopy perturbation method and the variational iteration method, for solving singular fractional partial differential equations of fractional order. The process of the methods which produce solutions in terms of convergent series is explained. The fractional derivatives are described in Caputo sense. Some examples are given to show the accurate and easily implemented of these methods even with the presence of singularities.